Insanity and Sanctity in Byzantium - Rotman, Youval (Cambridge, MA : Harvard University Press, 2016)
In the Roman and Byzantine Near East, the holy fool emerged in Christianity as a way of describing individuals whose apparent madness allowed them to achieve a higher level of spirituality. Youval Rotman examines how the figure of the mad saint or mystic was used as a means of individual and collective transformation prior to the rise is Islam.
Frontmatter -- Contents -- Prologue: Insanity and Religion -- Part I. Sanctified Insanity: Between History and Psychology -- 1. The Paradox That Inhabits Ambiguity -- 2. Meanings of Insanity -- Part II. Abnormality and Social Change: Early Christianity versus Rabbinic Judaism -- 3. Abnormality and Social Change: Insanity and Martyrdom -- 4. Socializing Nature: The Ascetic Totem -- Epilogue: Psychology, Religion, and Social Change -- Abbreviations -- Notes -- Bibliography -- Acknowledgments -- Index
Mode of access: Internet via World Wide Web.
In English.
Description based on online resource; title from PDF title page (publisher's Web site, viewed Feb. 24, 2017)
Keywords: Mental illness -- Religious aspects -- Byzantine Empire; Mental illness -- Social aspects -- Byzantine Empire; Psychology and religion -- Byzantine Empire; Religion and sociology -- Byzantine Empire